2020
DOI: 10.3390/nano10040716
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Strategies to Contact 3D Nano-Pillars

Abstract: This contribution explores different strategies to electrically contact vertical pillars with diameters less than 100 nm. Two process strategies have been defined, the first based on Atomic Force Microscope (AFM) indentation and the second based on planarization and reactive ion etching (RIE). We have demonstrated that both proposals provide suitable contacts. The results help to conclude that the most feasible strategy to be implementable is the one using planarization and reactive ion etching since it is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While the filling factor remains large, contact resistance is large, possibly because of the improvable polymerization and polishing procedures. As an alternate strategy, Amat et al reported on the successful fabrication of metallic contacts on polymer-embedded NPs by using reactive-ion etching (RIE) to uncap NP tips [17]. Upon accurate optimization of RIE conditions (power, duration, and cycles), O 2 plasma enabled the selective removal of the polymer (a photolithographic resist) while preserving Si NPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the filling factor remains large, contact resistance is large, possibly because of the improvable polymerization and polishing procedures. As an alternate strategy, Amat et al reported on the successful fabrication of metallic contacts on polymer-embedded NPs by using reactive-ion etching (RIE) to uncap NP tips [17]. Upon accurate optimization of RIE conditions (power, duration, and cycles), O 2 plasma enabled the selective removal of the polymer (a photolithographic resist) while preserving Si NPs.…”
Section: Discussionmentioning
confidence: 99%
“…As a second possibility, we embedded NP forests into a polymeric matrix, obtaining mechanically stabilized elements that could be used as conventional thermoelectric legs in TEGs and thermoelectric cool-ers (TECs). It should be mentioned that alternate approaches have been reported in the literature [17], which will be discussed and compared to electroplating and embedding.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of dielectric characteristics, relative permeability (κ) values in the range of 2.8-5.1 have been reported [30]. The topography that arises due to the NPs precludes a good planarization; consequently, a method based on first producing a thicker HSQ layer and afterwards etching it back by means of diluted hydrofluoric acid (HF) is used [31,32]. The final HSQ thickness accuracy is determined by the precision of the etch-rate.…”
Section: Vertical Set Integration Processmentioning
confidence: 99%
“…Pillar fabrication has been demonstrated by combination of DSA with tone-inversion [ 126 , 127 ], by sequential infiltration synthesis in BCPs [ 128 , 129 ], and directly by pattern transfer of the BCP template [ 130 ]. As we approach the most extreme semiconductor nodes in terms of scaling, alternative architectures and devices such as vertical gate-all-around field-effect transistors (GAA FETs) or single-electron transistors (SETs) are entering into discussion [ 131 ], which could be potentially fabricated by DSA.…”
Section: Block Copolymers For the Fabrication Of Functional Devicementioning
confidence: 99%